THE INFLUENCE OF AUDIT QUALITY ON EARNING MANAGEMENT IN MANUFACTURING COMPANIES ON THE IDX FOR 2017-2019 PERIODS - Kurniawan, Karel Sava; Antonio, Dr. Gregorius Rudy (jfpublisher, 2022)
The focus of this study is to investigate and obtain the empirical evidence about the impact of audit quality on earning management. The measurement of audit quality is proxied into two parts, called the size of KAP and auditors of industry specialization, the size of auditors is formulated using a dummy variable where the company audited by Big- 4 is given code 1 while the company audited by Non-Big-4 is given code 0. For industrial specialization auditors, they are formulated using a dummy variable where if the market share is more than equal to 20%, code 1 will be given and code 0 is given less than 20%. The object in this study is a company engaged in the manufacturing sector that has gone public and is listed on the Indonesia Stock Exchange. The sampling method used was a non-probability purposive judgmental sample and resulted in 104 companies that met the requirements for research. he data were analyzed based on the range of years from 2017, 2018 and 2019. The method of multiple linear regression analysis was used for data analysis and hypothesis development, giving rise to research results that: 1) KAP size does not have a negative effect on earning management, and (2) specialized auditors industry has no negative effect on earnings management.